Human leukocyte antigen-G isoform HLA-G2/6, but not HLA-G1/4/5, is an independent indicator of poor survival in patients with colorectal cancer - Zhang, Xia; Han, Qiu-Yue; Zhang, Jian-Gang; Lin, Jiao; Yan, Wei-Hua; Lin, Aifen (Frontiers in Immunology, 2025)
BackgroundHuman leukocyte antigen (HLA)-G has multiple isoforms with unique molecular structures and receptor-binding specificities. Different HLA-G isoform(s) may have distinct clinical relevance. Because of the lack of isoform-specific monoclonal antibodies (mAbs), the clinical significance of HLA-G isoforms (HLA-G1 to HLA-G7), except HLA-G1 and HLA-G5, remains largely unknown.MethodsIn this study, mAbs against HLA-G2/6 and HLA-G1/4/5 isoforms were generated and characterized. Expression of HLA-G2/6 and HLA-G1/4/5 isoforms was analyzed by immunohistochemistry, and clinical significance was evaluated retrospectively in 345 patients with colorectal cancer (CRC).ResultsThe expression rate of HLA-G2/6 (90/345, 26.1%) was significantly lower than that of HLA-G1/4/5 (275/345, 79.7%; p < 0.001). Patients with HLA-G2/6 expression had significantly poorer overall survival (OS) (median OS: 6.3 years [95% CI: 4.1–8.5] vs. 10.0 years [95% CI: 7.6–12.4]; p = 0.008). Multivariate Cox proportional-hazard model results indicated that HLA-G2/6 was an independent prognostic factor for CRC (hazard ratio [HR] = 1.530, 95% CI: 1.125–2.081; p = 0.007). Moreover, HLA-G2/6 expression showed stratified prognostic significance among several CRC patient subgroups, specifically in female patients (p = 0.003), younger patients (<66 years p < 0.001), patients with colon cancer (p = 0.045), those at stage pT3 (p = 0.008), pN1 (p = 0.020), pM0 (p = 0.009), and AJCC stage III (p = 0.005). However, no statistical significance was found between HLA-G1/4/5 isoform expression and patient prognosis in CRC.ConclusionsThis is the first study to generate mAbs for the HLA-G2/6 and HLA-G1/4/5 isoforms. Our findings reveal that HLA-G2/6—but not HLA-G1/4/5—expression is an independent prognostic indicator for patients with CRC. In the context of precision medicine, our study also suggests that HLA-G isoform typing may be necessary for HLA-G-targeted cancer immunotherapy.